Persecuting Bill. (Economist)
U.S. trustbusters are right to be concerned about Microsoft's efforts to tighten its hold on the personal computer (PC). Judge Thomas Jackson was probably correct to prevent Microsoft from demanding that PC manufacturers install its Internet browser as a condition for licensing Windows 95. It is too simple to maintain that he who controls the browser market also controls the Web, but browsers do form a kind of gateway that can affect how people use the Internet by promoting some content to the detriment of others. Furthermore, Microsoft's critics assert, and Microsoft fervently denies, that it is determined to use its browser to stop Java, a new software language whose supporters claim for it a “write once, run anywhere” capability, from reaching its potential. Sun Microsystems, which invented Java, is suing Microsoft for trying to split up Java into various versions.